Prevalensi Phoria Dan Tropia Pada Anak Usia Sekolah Dasar Di SDN Duri Kepa 16 Pagi dan SDN 17 PG Di Kelurahan Duri Kepa Jakarta Barat Tahun 2024 - Lede, Cindy Alfaranti Gracelia; Silaen, Desi Hartati (Jurnal MedScientiae, 2025)
This study aims to determine the prevalence of phoria and tropia in elementary school-aged children at SDN Duri Kepa 16 Pagi and SDN 17 PG in Duri Kepa Village, West Jakarta. The research design used was quantitative descriptive with a cross-sectional approach. A total of 601 children were the subjects of this research. Data was collected using an occluder to detect phoria and Tropical disorders in children. The results showed that the prevalence of exotropia was 0.7% at long distances and 0.8% at near distances, and esotropia was 0.3% at long distances and near distances. The prevalence of orthophoria was found in 99% of children. This research provides recommendations that routine checks for visual impairment in children be carried out from an early age